2017
DOI: 10.18632/oncotarget.16701
|View full text |Cite
|
Sign up to set email alerts
|

Clinical verification of plasma messenger RNA as novel noninvasive biomarker identified through bioinformatics analysis for lung cancer

Abstract: Lung cancer (LC) remains associated with significant mortality worldwide. The lack of reliable noninvasive biomarkers and targeted therapies contributes to poor survival rate. Herein, we initially took advantage of the public microarray data from Oncomine database to filter messenger RNAs (mRNAs) as potential biomarkers. Subsequently, clinical validation was applied to identify candidate noninvasive biomarkers in plasma from patients with LC. Through comprehensive analysis of transcriptional expression profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…Salivary mRNA of COL3A1 also showed an opposite expression pattern in OSCC tissues (GSE13601 and GSE37991). A previous study has shown that mRNA expression trends can vary between tissue RNA and plasma circulating RNA [30]. Because the potential differences in mRNA expression between tumor tissues and saliva cannot be easily deduced, further study is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Salivary mRNA of COL3A1 also showed an opposite expression pattern in OSCC tissues (GSE13601 and GSE37991). A previous study has shown that mRNA expression trends can vary between tissue RNA and plasma circulating RNA [30]. Because the potential differences in mRNA expression between tumor tissues and saliva cannot be easily deduced, further study is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of receiver operating characteristic (ROC) curves were used to evaluate the candidate biomarker diagnostic value as previously described. 8 Differences were considered significant at P < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Since it was first demonstrated in the 1990s by Lo et al, circulating cell-free messenger RNA has been used to detect diagnostic and prognostic biomarkers in various cancers, including lung, nasopharyngeal, and colorectal cancers. 7,8 In addition, March-Villalba et al 9 showed that plasma telomerase reverse transcriptase (hTERT) mRNA can be a useful biomarker for the diagnosis and prediction of prognosis in PCa patients. The above studies suggested that cell-free RNA in plasma may play a vital role in cancer diagnosis and prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The establishment of high-throughput molecular database such as microarray databases brings a new approach for biomarker identification. We have previously published an effective bioinformatics scheme to identify noninvasive biomarkers for lung cancer (Zhou et al 2017). In the present study, we applied the similar approach to explore mRNAs circulated in plasma from patients with GC as potential biomarkers.…”
Section: Introductionmentioning
confidence: 99%